Preparation and characterization of low-cost high-performance mullite-quartz ceramic proppants for coal bed methane wells - Wang Kaiyue; Wang Huijun; Zhou Yi; Li Guomin; Wu Yaqiao; Hao Jianying; Tian Yuming (Science and Engineering of Composite Materials, 2018)
In this study, the mullite-quartz-based proppants were successfully prepared by using the coal gangue as the raw materials. Then, the effects of the additive and the sintering temperature on the composition, microstructure, and properties of the proppants were investigated. Results showed that the proppants sintered at 1250°C with the 10 wt% bauxite additive presented the best performance, which was very close to that of the quartz-proppant, and met the operational requirements of the 52 MPa coal bed methane wells. The viscous flow mechanism of the liquid phase formed during the sintering process also promoted the arrangement of the grains, thus benefiting the densification and the strength of the proppants.